(untitled) (CIPEEX, 2026)
Metformin (MET), a member of the biguanide class, is widely used in the treatment of type 2 diabetes and can exist in different tautomeric forms. This study aimed to investigate the MET-t1 and MET-t2 tautomers, with an emphasis on their structural characteristics in a vacuum. For this purpose, Density Functional Theory (DFT) calculations and Car-Parrinello Molecular Dynamics (CPMD) simulations were performed, with an analysis of bond lengths and electronic stability. In MET-t1, the CPMD simulations revealed a dynamic transfer of the H5 proton from N17 to N19, accompanied by an electronic redistribution in the conjugated system. This process resulted in the shortening of the C1–N17 and C2–N16 bonds and the lengthening of C1–N18 and C2–N19, which characterizes an active resonance that is dependent on the protonic state. In contrast, MET-t2 remained stable throughout the simulation, with constant N–H lengths and the presence of two well-defined C=N bonds (C1–N15 and C2–N17), which are associated with a rigid and localized π conjugation. The comparison between the methods showed good agreement, highlighting the CPMD’s ability to describe protonic phenomena that are not captured by DFT. It is concluded that MET-t1 exhibits a more dynamic behavior and is more susceptible to tautomerization, while MET-t2 is configured as a more stable and electronically rigid tautomer.